Outcome of the Management of Patients with Venereal Diseases in the Public Health Region 3 in 2006 - จันทรปราสาท สายรุ้ง (Disease Control Journal, 2007)
The objective of this study was to evaluate the medical treatment of venereal patients who attended the government hospital in public health region 3. The standard treatment guideline , year 2003 was used as gold standard. This retrospective study was conducted by reviewing OPD cards from patients during October 2005 to September 2006. Collected data was analyzed by SPSS program for windows. It was found that the STI clinic at the Office of Prevention and control had 98.1% overall correct treatment according to the guideline compared to only 52.8% from the center hospital and general hospital and 40% from the community hospitals. For the specific diseases, The STI clinic of the OPC, No. 8 yielded more than 90% in gonorrhea, non-gonococcal urethritis and chancroid. while the center hospital and general hospital yielded more than 90% in syphilis. The community hospitals had not achieved 90% in all diseases.